Identitas nasional: keberagaman dalam kebhinekaan - Febriani, Shelvy Fransiska (Maliki Interdisciplinary Journal, 2025)
National identity is essentially a manifestation of cultural values that grow and develop in aspects of the life of a nation (nation). The elements of national identity are ethnicity, religion, culture and language. The function of national identity is to strengthen a sense of pride in the country and culture, build solidarity among citizens, advance sustainable social, economic and political development, maintain state sovereignty, and improve relations between nations. Pancasila is the basis of the nation’s personality. As the basis of the State, all social, national and state life must reflect the values of Pancasila, and as the personality of the nation, all attitudes, behaviors and actions of Indonesian citizens must be an implementation of the values of Pancasila. This material discusses diversity in diversity in differences in religion, ethnicity, culture, language and others. The method used is the library research method. With a qualitative approach, namely literature studies, information collection by reviewing sources related to diversity and diversity in Indonesia. By understanding diversity in diversity, individuals can broaden their horizons, increase empathy, encourage tolerance, understand and accept diversity, and strengthen the sense of national unity.